Claim Settlement of Life Insures in Nepal - Basaula, Damodar (Janapriya Journal of Interdisciplinary Studies, 2017)
Claim management has been vital area of the life insurance business. Life insurance of Nepal seems still in infant stage; however the success of life insurance companies may largely depend upon the claim management. This paper has attempted to state and analyze five years’ status of the performance of claim settlement made by life insurers especially on the basis of total claim received; claim paid and claim outstanding aspects. This paper describes the status of current situation of claim settlement in life insurance market. The literature review indentified the lapses and gaps of the claim settlement in Nepalese Life Insurance Companies. The study concludes that present claim settlement status of Nepal has been seen in growing stage of development in terms of total claim. Some of the life insurers have made tremendous improvement in paying claim in the range of 90.96% to 98.49%. Some life insurers established earlier have not demonstrated well performance in settling claim and some newly set companies have made satisfactory growth. Janapriya Journal of Interdisciplinary Studies, Vol. 5 (December 2016), page: 27-43